Anti‐inflammatory effects of melatonin in multiple sclerosis. (26th August 2016) - Farez, Mauricio F.; Calandri, Ismael L.; Correale, Jorge; Quintana, Francisco J.
Abstract : Melatonin is a hormone with complex roles in the pathogenesis of autoimmune disorders. Over the years, it has become clear that melatonin may exacerbate some autoimmune conditions, whereas it alleviates others such as multiple sclerosis. Multiple sclerosis is an autoimmune disorder characterized by a dysregulated immune response directed against the central nervous system. Indeed, the balance between pathogenic CD4 + T cells secreting IFN‐γ (TH 1) or IL‐17 (TH 17); and FoxP3 + regulatory T cells and IL‐10 + type 1 regulatory T cells (Tr1 cells) is thought to play an important role in disease activity. Recent evidence suggests that melatonin ameliorates multiple sclerosis by controlling the balance between effector and regulatory cells, suggesting that melatonin‐triggered signaling pathways are potential targets for therapeutic intervention. Here, we review the available data on the effects of melatonin on immune processes relevant for MS and discuss its therapeutic potential. Abstract : Melatonin synthesis is stimulated by darkness and inhibited by light. Thus, melatonin levels are seasonal with higher levels in fall and winter. Recently, melatonin levels have been linked to multiple sclerosis disease activity. Melatonin may affect multiple sclerosis and potentially other autoimmune disorders by boosting or suppressing several immune cell subsets.